Complex interactions of cellular players in chronic Graft-versus-Host Disease - Gail, Laura Marie; Schell, Kimberly Julia; Łacina, Piotr; Strobl, Johanna; Bolton, Steven J.; Steinbakk Ulriksen, Emilie; Bogunia-Kubik, Katarzyna; Greinix, Hildegard; Crossland, Rachel Emily; Inngjerdingen, Marit; Stary, Georg (Frontiers in Immunology, 2023)
Chronic Graft-versus-Host-Disease is a life-threatening inflammatory condition that affects many patients after allogeneic hematopoietic stem cell transplantation. Although we have made substantial progress in understanding disease pathogenesis and the role of specific immune cell subsets, treatment options are still limited. To date, we lack a global understanding of the interplay between the different cellular players involved, in the affected tissues and at different stages of disease development and progression. In this review we summarize our current knowledge on pathogenic and protective mechanisms elicited by the major involved immune subsets, being T cells, B cells, NK cells and antigen presenting cells, as well as the microbiome, with a special focus on intercellular communication of these cell types via extracellular vesicles as up-and-coming fields in chronic Graft-versus-Host-Disease research. Lastly, we discuss the importance of understanding systemic and local aberrant cell communication during disease for defining better biomarkers and therapeutic targets, eventually enabling the design of personalized treatment schemes.